Hygiene system modeling for toileting in schools - Crocker, J.; Walters, J.; Chipungu, J.; Bhagwan, J.; Dione, Michel M.; Dreibelbis, R.; Dumlao, M.C.; Faruque, A.S.G.; Flint-O'Kane, M.; Gautam, O.P.; Lakhe, N.A.; Muga, R.; et al. (Elsevier, 2025)
Background: Hygienic toileting is associated with positive health outcomes; yet efforts to provide the necessary preconditions for this behavior, namely provision of anal cleansing materials, a well-maintained toilet facility, and handwashing, are often limited—especially in schools—by a complex set of determinants and upstream factors that hinder access to the materials and behavioral drivers required for effective practice. Systems thinking, and its associated tools, is one approach to understanding and developing interventions to address the complexity of an interconnected set of factors impacting hygiene program outcomes.